NUMERICAL INVESTIGATION ON FLEXURAL PERFORMANCE OF BUILT-UP STEEL BEAMS WITH DIFFERENT WEB OPENINGS - Hussein Talab Nhabih; Mohammad R.K.M. Al-Badkubi; Marwa Marza Salman (International Journal for Computational Civil and Structural Engineering)
Recently, the usage of Structural Steel Beams with Opening in the Web has spread extensively in all over the world, in various types of buildings such as high-rise buildings and industrial buildings. There are several advantages in using openings in beams. There for, an analytical investigation was carried out on fourSteel Beams with Opening (SBWO) models by using a powerful nonlinear simulation software ABAQUS. The initiative was to study the overall flexural behaviour of (SBWO’s) and to establish the maximum load carrying capacity, and deflection. Only vertical loads have been considered in the (SBWO’s) performance investigation. The Built-Up sections were tested up to failure. The simulated models were considered to be under simply supported condition at their edges and a uniform distributed load were applied over the upper flange of the beam along all beam's length. The flexural behaviour of beams with different opening shapes were tested and compared. The test results proved to be very useful in selecting the opening shape.